The Depletion of ABI3BP by MicroRNA-183 Promotes the Development of Esophageal Carcinoma - Hongfei Cai; Yang Li; Da Qin; Rui Wang; Ze Tang; Tianyu Lu; Youbin Cui (Mediators of Inflammation)
Background. Esophageal cancer (EC), as a serious threat to human life and health, is one of the most common cancers around the world. Many studies have suggested that many microRNAs are involved in tumorigenesis and progression. Methods. To search for a novel and promising predictive therapeutic target or biomarker to achieve the goal of the early diagnosis and treatment of EC, we used the EC cell lines Eca-109 and KYSE-150 and normal human esophageal epithelial cells (HEECs) to investigate the effect of ABI3BP on EC. Results. We found that ABI family member 3 binding protein (ABI3BP) was downregulated in EC and suppressed the proliferation, activity, migration, and invasion of EC cells. ABI3BP was downregulated by miR-183, which plays the role of an oncogene. Conclusion. ABI3BP and miR-183 can be considered potential biomarkers for the diagnosis of patients with EC and can be effective targets for antitumor therapy.